DESIGNING AN ANDROID-BASED DIGITAL MUSEUM APPLICATION AS A VIRTUAL VISIT TO THE MUSEUM - Yuliska Yuliska; Asyrul Fikri (IJISCS (International Journal of Information System and Computer Science), 2022)
The Sang Nila Utama Museum is one of the most comprehensive museums in Riau Province. Currently, the Sang Nila Utama Museum has more than 4000 collections divided into ten classifications:  Geology, Biology, Ethnography, Archeology, Historics, Numismatics, Philology, Ceramics, Arts, and Technology. From founded in 1991 to 2018, visits to Sang Nila Utama Museum can be done offline; however, since the COVID-19 pandemic began to enter Pekanbaru City, Sang Nila Utama Museum has been closed to the public. With the closure of the Sang Nila Museum, the museum's function as an educational tour, cultural and heritage tourism has been inhibited. The digital museum application is a solution to make museum visits no longer limited to offline visits but can also be done virtually. The application exhibits all museum collections, which consist of ten classifications, with a total collection of nearly 300 collections. Based on the test results, the digital museum application got good responses from the users and has met the five aspects of usability testing with an average usability value above four which is above the median value on a scale of five.